Dry Reforming of Methane with Mesoporous Ni/ZrO2 Catalyst - Subhan Azeem; Rabya Aslam; Mahmood Saleem (International Journal of Chemical Engineering)
Dry reforming of methane has exhibited significant environmental benefits as it utilizes two major greenhouse gases (CO2 and CH4) to produce synthesis gas, a major building block for hydrocarbons. This process has gained industrial attention as catalyst deactivation due to coke deposition being a major hindrance. The present study focuses on the dry reforming of methane over Ni-supported mesoporous zirconia support. Ni metal was loaded over in-house synthesized mesoporous zirconia within the 0–15 wt% range using the wet impregnation method. The physicochemical properties of the synthesized catalysts were studied using various characterization techniques, namely, XRD, SEM, FTIR, TGA, and N2 adsorption-desorption techniques. The activity of all the catalysts was evaluated at 750°C and gas hourly space velocity (GHSV) of 72000 ml/h/gcat for 9 hours (540 min). The deactivation factor indicating a loss in conversion with time is reported for each catalyst. 10 wt% Ni/ZrO2 showed the highest feed conversion of about 68.8% for methane and 70.2% for carbon dioxide and the highest stability (15.1% deactivation factor and 21% weight loss) for dry reforming of methane to synthesis gas.